The Impact of Digital Banking and Financial Expertise on Financial Integration in India (International Journal of Food and Nutritional Sciences, 2022)
Every company in every sector faces issues as a result of digitization.Fintech projects are regarded as more important innovations in the financial industry, resulting from the evolution of the digital revolution. These projects are progressing quickly due to the divisionof economic system, systems, and computer technology. Blockchain investigation is yet in its early stages. However, fintech provides various services, including e-aggregators, e-trade, e-indemnity, financing, payments (including digital wallets), and cryptocurrency like Bitcoin. It offers a chance to look more deeply at the difficulties and developments in fintech study. India must enhance financial accessibility to reach the under-banked portions of the populace and offer a steady setting for financial technology companies. Both correlation and regression analyses were utilized in this research, jointly with secondary information obtained from the Reserve Bank of India, to analyze this impact. The objective was to ascertain how digital and fintech services would affect the inclusion of money in India. The findings show that fintech companies have greatly boosted the availability of finance in this country, particularly for the middle class. These results will workhard to integrate eachstate resident into a plannedfinancial structure.